Abamectin resistance in strains of vegetable leafminer, Liriomyza sativae (Diptera: Agromyzidae) is linked to elevated glutathione S‐transferase activity. (7th April 2014) - Wei, Qing‐Bo; Lei, Zhong‐Ren; Nauen, Ralf; Cai, Du‐Cheng; Gao, Yu‐Lin
Abstract: Abamectin resistance was selected in the vegetable leafminer, Liriomyza sativae (Blanchard) (Diptera: Agromyzidae) under laboratory conditions, and cross‐resistance patterns and possible resistance mechanisms in the abamectin‐resistant strains (AL‐R, AF‐R) were investigated. Compared with the susceptible strain (SS), strain AL‐R displayed 39‐fold resistance to abamectin after 20 selection cycles during 25 generations, and strain AF‐R exhibited 59‐fold resistance to abamectin after 16 selection cycles during 22 generations. No cross‐resistance to cyromazine was found in both abamectin‐resistant strains. However, we failed to select for cyromazine resistance in L. sativae under laboratory conditions by conducting 17 selection cycles during 22 generations. However, moderate levels of cross‐resistance to abamectin (6–9 fold) were observed in strains which received cyromazine treatments. Biochemical analysis showed that glutathione S‐transferase (GST) activity in both abamectin‐resistant strains (AL‐R, AF‐R) was significantly higher than in the susceptible strain (SS), suggesting metabolically driven resistance to abamectinin L. sativae . Recommendations of mixtures or rotation of cyromazine and abamectin should be considered carefully, as consecutive cyromazine treatments may select for low‐level cross‐resistance to abamectin.